Survey of adrenal crisis associated with inhaled corticosteroids in the United Kingdom. Issue 6 (1st December 2002) - Todd, G R G; Acerini, C L; Ross-Russell, R; Zahra, S; Warner, J T; McCance, D
Abstract : Background: Until recently, only two cases of acute adrenal crisis associated with inhaled corticosteroids (ICS) had been reported worldwide. We identified four additional cases and sought to survey the frequency of this side effect in the United Kingdom. Methods: Questionnaires were sent to all consultant paediatricians and adult endocrinologists registered in a UK medical directory, asking whether they had encountered asthmatic patients with acute adrenal crisis associated with ICS. Those responding positively completed a more detailed questionnaire. Diagnosis was confirmed by symptoms/signs and abnormal hypothalamic-pituitary-adrenal axis function test results. Results: From an initial 2912 questionnaires, 33 patients met the diagnostic criteria (28 children, five adults). Twenty-three children had acute hypoglycaemia (13 with decreased levels of consciousness or coma; nine with coma and convulsions; one with coma, convulsions and death); five had insidious onset of symptoms. Four adults had insidious onset of symptoms; one had hypoglycaemia and convulsions. Of the 33 patients treated with 500–2000 μg/day ICS, 30 (91%) had received fluticasone, one (3%) fluticasone and budesonide, and two (6%) beclomethasone. Conclusions: The frequency of acute adrenal crisis was greater than expected as the majority of these patients were treated with ICS doses supported by British Guidelines on Asthma Management. Despite being the least prescribed and most recently introduced ICS, fluticasone was associated with 94% of the cases. We therefore advise that the licensed dosage of fluticasone for children, 400 μg/day, should not be exceeded unless the patient is being supervised by a physician with experience in problematic asthma. We would also emphasise that until adrenal function has been assessed patients receiving high dose ICS should not have this therapy abruptly terminated as this could precipitate adrenal crisis.